How to Share it out: The Value of Information in Teams - Alex Gershkov; Jianpei Li; Paul Schweinzer (Center for Economic Studies and ifo Institute (CESifo), 2014)
We study the role of information exchange, leadership and coordination in team or partnership structures. For this purpose, we view individuals jointly engaging in productive processes a team' as endowed with individual and privately held information on the joint production process. Once individual information is shared, team members decide individually on the effort they exert in the joint production process. This effort, however, is not contractible; only the joint output (or profit) of the team can be observed. Our central question is whether or not incentives can be provided to a team in this environment such that team members communicate their private information and exert efficient productive efforts on the basis of this communication. Our main result shows that there exists a simple ranking-based contract which implements both desiderata in a wide set of situations.
Keywords: C70; D70; D80; L20; 330; moral hazard; adverse selection; leadership; teams